IDENTIFIKASI HAMBATAN PENGUKUHAN KAWASAN HUTAN DI PROVINSI RIAU - Eno Suwarno (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2017)
The certainty of the status of forest area is an important prerequisite for the realization of good forest governance. However due to the error procedure in determining forest area in the past, which until now has not been improved, becoming one of the major obstacles to realizing that prerequisite. The study aim to identify the main obstacles of designation of forest areas in Riau Province, by using explanative research format and historical approach, while secondary data were collected from various sources. The time range study started in 1967 until 2015. The study found that the main obstacle was due to latent conflict on forest tenure between central government and other parties that have not been resolved. Conflict was begun with the issuance of Ministerial Decree number 173/Kpts-II/1986 on Consensus-based Forest Land Use Planning that sets throughout the Riau province into forest areas. Besides, the regulatory regime on the affirmation of the existing forest area currently tend to be used as an instrument of affirmation of the right on the land rather than to set-up functions of forests.This point of view impact to the difficulty of completing the boundary demarcation task and establishment of forest area in the field.